Födovalspreferenser hos en arktisk specialist - Elfvenfjärd, Beatrice; Åmansson, Erika (2022)
The Arctic tundra has many unexplored areas. Due to the harsh climate and the difficult accessibility, there is a lack of knowledge about the different species that live under these circumstances. Herbivores in this environment have a large effect on the plant community, one of these is the moth butterfly larva Gynaephora groenlandica. In the event of an outbreak of the moth butterfly population, they occur in large numbers and can have a negative effect on plants reproductive ability. With its unique life cycle of 14 years with short foraging periods, they must efficiently obtain energy through food to survive the long dormancy periods. This report examines the Arctic specialist G. groenlandica’s food preferences in its larval stages and tries to explain the food preference in order to contribute to increased knowledge and understanding of the subject. This with the help of a nochoice experiment for collected data from Wrangel Island and values for various plant traits from among other things database TRY. The results showed that the larvae prefer the willow genus and also Rhodiola integrifolia, Dryas octopetala and one species of Potentilla over others. But there is no signification that the different plant characteristics affect this preference. What this is based on is difficult to answer. Phylogenetic signal, temperature variations, variation in nutrient quality, light availability and chemical defence substances may be some explanations for this.